House prices, housing development costs, and the supply of new single-family housing in German counties and cities - Oliver W. Lerbs (Westfälische Wilhelms-Universität Münster, Centrum für Angewandte Wirtschaftsforschung (CAWM), 2012)
This paper employs panel data on 413 German counties and cities from 2004 to 2009 to investigate the supply of new single-family housing in local housing markets. New local housing supply is measured by the annual number of construction permits in relation to the existing single-family housing stock. This supply indicator is econometrically related to existing home prices and new housing development costs, which include the costs of housing construction and vacant land in a given location. The results suggest that both higher prices for existing homes and recent increases in development costs are positively associated with local single-family home permit rates. Instead, higher levels of development costs turn out to dampen construction activity. The average local price elasticity of new single-family home supply is considerably less than one, with surprising differences across the urban hierarchy.
Keywords: R12; R31; C31; 330; new housing supply; local housing markets; panel data